Pengaruh gaya belajar kinestetik terhadap hasil belajar tematik kelas 4 tema 3 di SDN 01 Manisrejo - Kiki Eviana Effendi; Nur Samsiyah; Tri Wahyuni Chasanatun (Prosiding Konferensi Ilmiah Dasar, 2022)
This study aims to identify and identify the kinesthetic learning styles in grade 4 SDN 01 Manisrejo in addition to identifying this research to determine whether there is a relationship between the influence of kinesthetic learning styles on thematic learning outcomes. This research includes quantitative research using experimental research methods using the Quasi Experiment method. In this study, the sample was divided into two groups, namely the control class and the experimental class. The samples in this study were students in class 4a and class 4b at SDN 01 Manisrejo, class 4a as the experimental class and class 4b as the control class. This study uses the matching only posttest control group design type of research. In this study, the instrument used for assessment was using a questionnaire or questionnaire and a posttest was given to all samples according to the characteristics of the kinesthetic learning style. The results of the analysis showed that the results of the data analysis of the experimental class and the control class showed that the kinesthetic learning style had a significant effect on the thematic learning outcomes of the fourth grade students of SDN 01 Manisrejo. The results obtained are tcount = 4.53 2.01808 = ttable with a significance level of 0.05 or 5% so that it can be  concluded that kinesthetic learning styles have an effect on thematic learning outcomes.